Active Controlling of Aerodynamic Bridges by Winglets - Phan , Đức Huynh; Nguyễn , Hoàng Sơn (Journal of Technical Education Science, 2010)
Flutter and buffeting are two hazard phenomena that commonly happen to suspension bridge. When the frequency of heaving is nearly equal to frequency of pitching, the flutter phenomenon will appear. While the flutter phenomenon is appearing, the displacement will be increased by the time. In addition the turbulent flow appears, it takes the buffeting phenomenon out. An active controlling method by winglets is a new method, it uses more two winglets to assemble in both sides of bridge, when having displacement, winglets will be controlled actively with suitable angle to create forces to suppress the vibration of bridge